Flour babies Anne Fine.. - Fine, Anne. (Ecclesiastes, 1994)
When his class of underachievers is assigned to spend three torturous weeks taking care of their own "babies" in the form of bags of flour, Simon makes amazing discoveries about himself while coming to terms with his long-absent father.